Does Reality TV Induce Real Effects? On the Questionable Association Between 16 and Pregnant and Teenage Childbearing - David A. Jaeger; Theodore J. Joyce; Robert Kaestner (Institute for the Study of Labor (IZA), 2016)
We reassess recent and widely reported evidence that the MTV program 16 and Pregnant played a major role in reducing teen birth rates in the U.S. since it began broadcasting in 2009 (Kearney and Levine, American Economic Review 2015). We find Kearney and Levine's identification strategy to be problematic. Through a series of placebo and other tests, we show that the exclusion restriction of their instrumental variables approach is not valid and find that the assumption of common trends in birth rates between low and high MTV-watching areas is not met. We also reassess Kearney and Levine's evidence from social media and show that it is fragile and highly sensitive to the choice of included periods and to the use of weights. We conclude that Kearney and Levine's results are uninformative about the effect of 16 and Pregnant on teen birth rates.
Keywords: J13; L82; 330; teen childbearing; media; social media; internet